Unfurling the diversity of the Neotropical fern genus Danaea (Marattiaceae) - Keskiniva, Venni (fi=Turun yliopisto|en=University of Turku|, 2024)
Tropical rainforests are at the same time some of the most species-rich and the least known terrestrial ecosystems. They are also under immense human pressure. Lack of information about species taxonomy, their distributions, and their relationships to environmental variables hinders conservation efforts. In Amazonia, the world's largest rainforest, ferns have been used as indicators of the soil, which determines the forest types of the region. That is why this dissertation focuses on Danaea (Marattiaceae), a fern genus with a distribution across tropical America, whose species seem to show soil specialization. However, the unclear state of taxonomy of the genus has led to a situation where individuals have been identified mainly at the level of three subgenera, which has inhibited the use of these ferns as indicators. I investigated what species Danaea contains and where they occur by examining variation in morphology and molecular phylogenetics together with biogeography. I also studied the significance of hybridization as an evolutionary force within the genus. My research was based on phylogenetic analyses and herbarium samples from across the distribution of the genus. I accepted 79 species and 8 hybrids in Danaea, of which 24 species and 6 hybrids were described as new to science. Danaea is the most species rich around the Andean mountains and Central America. The difficult taxonomy of Danaea can be explained by hybridization as well as convergent evolution and/or conservation of morphology. A taxonomic revision utilizing molecular data helped separate the morphologically challenging genus into evolutionarily, biogeographically, and morphologically consistent species, which can be used in future research employing a new identification key. Hybridization appears to act both as a homogenizing and diversifying force within Danaea. One of the hybrids I found is a result of one of the possibly deepest known hybridization events in the biological world. My dissertation showed how molecular phylogenetic methods can accelerate the description of diversity. Many of the new species were already endangered at the time of description. Furthermore, following my revision the distribution areas of Danaea species are generally narrower than previously thought.